The effect of mechanization level and harvesting system on the thinning cost of Mediterranean softwood plantations - Spinelli, Raffaele; Lombardini, Carolina; Magagnotti, Natascia (Silva Fennica, 2014)
The study compared motor-manual cut-to-length (CTL) harvesting, motor-manual whole-tree (WT) harvesting, mechanized CTL harvesting and mechanized WT harvesting as applied to the production of energy chips from the second thinning of Mediterranean pine plantations in flat terrain. Mechanization increased productivity between 6 and 20 times, depending on process step. It also allowed reducing thinning cost by a factor 4. Shifting from CTL to WT harvesting resulted in a reduction of harvesting cost between 40 and 50%. Fuel consumption was between 40 and 100% higher for CTL harvesting than for WT harvesting. Mechanization entailed a reduction of fuel consumption between 10 and 40%. Stand damage was generally low, between 1.5 and 6%. Mechanized CTL harvesting resulted in the lowest incidence of wounding, and the difference between mechanized CTL and manual WT harvesting was statistically significant. Soil compaction was absent or very small, depending on treatment. Mechanized thinning may produce larger increases of soil bulk density, compared to motor-manual thinning, but the difference is small, although significant. CTL harvesting leaves a larger amount of biomass on the soil, which relieves possible concerns about soil nutrient depletion. On the other hand, heavy residue loads may increase fire risk especially in sensitive Mediterranean environments.